Hubungan Kebiasaan Mengonsumsi Kopi Dengan Terjadinya Stain Pada Masyarakat Di Desa Sirap (Jurnal Terapi Gigi dan Mulut, 2023)
Stain is a staining on the teeth caused by the attachment of food, drink, or other content, such as coffee. The habit of consuming coffee is one of the factors that cause stains due to caffeine contained in coffee. The purpose of this study was to determine the relationship between coffee consumption habits and the occurrence of stains on teeth. This type of research is analytic with a cross sectional research design which was carried out in March 2022 on 50 respondents with a sampling technique using purposive sampling technique. The habit of consuming coffee was obtained through interviews using a questionnaire, while stains on teeth were obtained through direct examination results. The results of univariate data showed that most of the respondents had stains with moderate criteria, namely 25 respondents (50%). The results of the Somers'd gamma test showed that there was a relationship between the length and amount of coffee consumed and the occurrence of stains, namely p < 0.05 and there was no relationship between the type of coffee consumed and the occurrence of stains, namely p > 0.05.